Optimal management of diabetic pregnancies and its current practice: a one-year study in a tertiary care center - Kiran, Pooja; Patil, Kamal P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Diabetes is one of the largest global health emergencies of 21st century and Gestational diabetes mellitus (GDM) is one of the most crucial illnesses complicating women of child-bearing age. The objectives of this study is to determine the maternal and fetal outcome of pregnancies complicated by maternal diabetes either GDM or pre-existing diabetes. Methods: An analysis of pregnant women was done retrospectively at KLES Dr. Prabhakar Kore Hospital and Medical Research Centre, Belgaum. 171 cases were diagnosed with diabetes mellitus in pregnancy. 162 cases developed GDM and 9 had pre-existing diabetes. Pregnant women who were found to be diabetic pre conceptionally or in the first trimester were classified as pre-existing diabetes. All pregnant women diagnosed with diabetes mellitus were studied and relevant maternal and fetal outcomes and complications were assessed. Results: There were171 diabetic women in this retrospective study out of which 94.7% had GDM and 5.26% had pre-existing diabetes. Rate of pre-eclampsia was 24.56%, preterm delivery was 17.54% and polyhydramnios was 15.20%. Rate of caesarean section were 57.30% and vaginal delivery was 45.06%. In fetal and neonatal complications, the rate of fetal macrosomia was 11.1%, hyperbilirubinemia 15.78%, respiratory distress syndrome 9.94%. Conclusions: Diabetes in pregnancy is associated with increased risks to the maternal and fetal complications. The aim of this study is to lay emphasis upon early detection, screening and timely management that will reduce the adverse outcomes in both mother and fetus. predicted.